What did the Disruptive Media Learning Lab ever do for us? - Kirsty Kift (Insights: The UKSG Journal, 2017)
Picture this. The Lanchester Library, Coventry University, 2014. The Disruptive Media Learning Lab (DMLL) opens on the top floor amongst a flurry of raised eyebrows and unanswered questions. ‘What is it?’, ‘Why is it in the Library?’ and ‘Who designed the wooden hill?’ Our Academic Liaison Librarian team were asked to move in there alongside a DMLL team comprising educational researchers and principal project leads, each specializing in a flavour of teaching practice such as open, flipped and gamification. A learning technologist, project and admin staff and student activators add to the mix. Still not sure what that would mean for a library? Neither were we. This article will take you through the reasons behind this alien landing, past the hill and the grass and onto the plains of what the DMLL ever did for the Library and our students.